Penerapan Metode Inkuiri Terbimbing Berbantuan Aplikasi PhET Untuk Meningkatkan Keterampilan Memecahkan Masalah Siswa - Suratna Suratna (Jurnal Teknologi Pembelajaran, 2023)
This research is entitled the application of the guided inquiry method with the PhET application to improve physics problem solving skills for class XII MIPA 1 SMA N 1 Pengasih for the academic year 2021/2022. The purpose of this study was to determine the quality of learning and learning outcomes in improving physics problem solving skills using the guided inquiry method with the PhET application in class XII MIPA 1 SMA N 1 Pengasih. This research is a classroom action research (CAR) which was conducted on 36 students of class XII MIPA 1 with two cycles and each cycle was carried out for three weeks. At the end of each cycle, students are given a test to measure their physics problem solving skills. The data collection instruments in this study were observation sheets, problem-solving skills tests and documentation. The results of this study indicate that there is an improvement in the quality of physics learning after applying the guided inquiry method with the PhET application so that it can improve physics problem solving skills for class XII MIPA 1 SMA N 1 Pengasih. Efforts to improve the physics problem solving skills of students of class XII MIPA 1 SMA N 1 Pengasih about the atomic nucleus and radioactivity after applying the guided inquiry method with the PhET application showed an increase in learning outcomes from 80.6% in the first cycle to 91.7% in the second cycle.